Evaluation of Audiological Results and Cochleo‐Vestibular Subclinical Injury After CO2 Laser Stapedotomy. Issue 9 (18th May 2021) - Mariani, Cinzia; Carta, Filippo; Piras, Nicoletta; Marrosu, Valeria; Serra, Federica; De Seta, Daniele; Puxeddu, Roberto
Abstract : Background and Objectives: Evaluation of the effectiveness and safety of CO2 laser stapedotomy, focusing on the audiological results, and on the surgical cochleo‐vestibular trauma. Study Design/Materials and Methods: Retrospective clinical trial on 38 patients with the diagnosis of otosclerosis, who underwent CO2 laser stapedotomy between January 2015 and October 2019. Postoperative air‐bone gap (ABG), mean air conduction gain, and postoperative changes of high frequency threshold were evaluated 1, 3, 6, and 12 months after surgery. Videoculography (VOG) was performed to assess the vestibular impairment preoperatively and 1 day, 1 week, and 1 month after surgery. Results: Postoperative ABG closure within 10 dB was obtained in 35 cases (92.1%), with a mean postoperative ABG of 4.4 dB and a mean air conduction improvement of 32.3 dB. No significant worsening of high frequency threshold was observed. Spontaneous nystagmus was found preoperatively in 5/38 patients (13.2%), 1 day after surgery in 13/38 patients (34.2%), 1 week after surgery in 12/38 patients (31.6%), and 1 month after surgery in 4/38 patients (10.5%). Positional nystagmus was found preoperatively in 12/38 patients (31.6%), 1 day after surgery in 25/38 patients (65.8%), 1 week after surgery in 22/38 patients (57.9%), and 1 month after surgery in 10/38 patients (26.3%). The occurrence of nystagmus did not always correlate with vestibular symptoms: after surgery, 10 patients (26.3%) experienced vertigo associated with dizziness, 8 patients (21.1%) suffered from dizziness without vertigo, and 14 patients (36.8%) showed nystagmus without any symptomatology. At 1 month after surgery none of the patients complained about vestibular symptoms. Conclusion: CO2 laser stapedotomy is a safe and effective technique, which allows to obtain good functional results with minimal perioperative cochleo‐vestibular trauma.© 2021 Wiley Periodicals LLC.